2018
DOI: 10.4103/0366-6999.239297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of RNA Interference Targeting STAT3 Gene Combined with Ultrasonic Irradiation and SonoVue Microbubbles on Proliferation and Apoptosis in Keratinocytes of Psoriatic Lesions

Abstract: Background:Signal transducer and activator of transcription 3 (STAT3) was strongly expressed and activated in psoriatic keratinocytes (KCs) and correlated with the severity of psoriasis. The study aimed to investigate the effects of STAT3 small interfering RNA (siRNA) combined with ultrasonic irradiation and SonoVue microbubbles on the proliferation and apoptosis in KCs of psoriatic lesions and the relative mechanisms.Methods:Psoriatic KCs were transfected under four experimental conditions: (1) STAT3 siRNA ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Silencing the STAT3 gene in psoriatic keratinocytes using siRNA, combined with ultrasound irradiation and microbubble technology, inhibits keratinocyte growth and induces apoptosis. 35 Transfection of keratinocytes, whether treated or untreated with avidin, with siRNA targeting Signal Transducer and Activator of Transcription 1 ( STAT1 ) and STAT3 , confirmed that avidin regulates psoriatic keratinocyte proliferation via the STAT signaling pathway. 36 Inhibiting Casein Kinase 2 ( CK2 ) suppresses both the STAT3 and Threonine Kinase ( AKT ) signaling pathways in human keratinocytes, which inhibits epidermal hyperplasia, abnormal differentiation, and the inflammatory response.…”
Section: Targeting Keratinocytesmentioning
confidence: 87%
“…Silencing the STAT3 gene in psoriatic keratinocytes using siRNA, combined with ultrasound irradiation and microbubble technology, inhibits keratinocyte growth and induces apoptosis. 35 Transfection of keratinocytes, whether treated or untreated with avidin, with siRNA targeting Signal Transducer and Activator of Transcription 1 ( STAT1 ) and STAT3 , confirmed that avidin regulates psoriatic keratinocyte proliferation via the STAT signaling pathway. 36 Inhibiting Casein Kinase 2 ( CK2 ) suppresses both the STAT3 and Threonine Kinase ( AKT ) signaling pathways in human keratinocytes, which inhibits epidermal hyperplasia, abnormal differentiation, and the inflammatory response.…”
Section: Targeting Keratinocytesmentioning
confidence: 87%
“…Antisense DNA or siRNA has promising preclinical results on suppressing the expression of a target gene, and different from unlike traditional medication, gene silencing through RNA interference (RNAi) using viral vectors can suppress targeted genes with a high selectivity and great potency [ 14 ]. However, the application of viral vectors has also stimulated great concern over its safety and efficiency due, as it could cause toxicity, immunogenicity, and tumorigenicity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For transfection using microbubble and ultrasound, SonoVue was used as previously described [ 14 ]. Six fluorinated sulfur (SF 6 ) was purchased from Bracco (Milan, Italy) and used as the agent of SonoVue (average diameter: 2.5 μm).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of another transfection method using ultrasonic irradiation and SonoVue microbubbles (US), SonoVue (Bracco, Italy), the phospholipid-encapsulated six fluorinated sulfur (SF6) with an average diameter of 2.5 μm was used as previously described [ 23 ]. Briefly, 5 ml normal saline and 50 μl siWISP1 or siNC were added into the SonoVue microbubble before use.…”
Section: Methodsmentioning
confidence: 99%